Substantiation of parameters of the mechanism of initial orientation of the package - Chervoniak, Vasyl (Видавництво Львівської політехніки, 2017)
The work is focused on solving the urgent problems of the packaging industry – the orientation of packaging. Structural and solid-state model of the mechanism of orientation is developed. The kinematic and force analysis of the primary orientation mechanism was carried out.
Keywords: kinematic analysis; force analysis; motion analysis; 3-D model; structural scheme